Socialization Of Blanded E-Learning Learning System On The College Of Kinesiology - Friska Sari Gracia Sinaga (Pusat Kajian Pendidikan Olahraga, Kesehatan dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Uiveristas Negeri Padang Jl. Prof. Hamka, Air Tawar Padang 25131 Telp. 0751-7059901, 2019)
Industrial Revolution 4.0 is a revolution that the currently touted by the government startingfrom the central government to the regional government. One of the things that can be done inimproving the quality of learning, especially at the university level, is through learning that is basedon learning through electronics. Electronic media that is intended is learning through blanded elearning that uses learning applications by utilizing technological advances as an effort in theimplementation of the industrial revolution that is being driven in the community and in thecampus environment. The purpose of the PPM (Community Devotion) program is carried out as atri dharma task of the tertiary institution and an effort to improve the competence of students,especially students in Sport Sciences at the Faculty of Sport Science, Cenderawasih University.The implementation of the PPM was carried out in July 2019, followed by 18 participants.The methods applied in this training are: lectures, demonstrations and practices using learningapplications based on e learning.The result is an increase in the competence of students, especially those who take kinesiologycourses in understanding teaching material so that it can spread the knowledge gained to theircolleagues and can then be applied to the workplace where he works later